Identification of Single Nucleotide Polymorphism and Pathway Analysis of Apolipoprotein A5 (APOA5) Related to Fatty Acid Traits in Indonesian Sheep - A. Gunawan; D. Anggrela; K. Listyarini; M. A. Abuzahra; Jakaria Jakaria; M. Yamin; I. Inounu; C. Sumantri (Tropical Animal Science Journal, 2018)
This study was aimed to identify single nucleotide polymorphism (SNP) and pathway analysis of APOA5 with fatty acids traits in sheep. A total of 47 rams consisted of 20 heads of Javanese Fat Tailed (JFT), 17 heads of Javanese Thin Tailed (JTT), and 10 heads of Garut Composite Sheep (GCS) were used in this study. Fatty acids traits were measured at the age of 12 months with the average body weight of 25-30 kg. Identification of polymorphism of APOA5 (g.26929941 C>T) gene were analyzed using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP). The pathway analysis of APOA5 gene was performed using Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. The SNP of APOA5 gene were found polymorphic with three genotypes (CC, CT, and TT). The gene frequency of CC, CT, and TT were 0.83, 0.11, and 0.06, respectively. The chi square test revealed that the locus of APOA5 (g.26929941 C>T) was in Hardy-Weinberg equilibrium, except in thin tailed sheep. The chi-square values of JFT, JTT, and GCS were 0.05, 0.03, and 0.04, respectively. A SNP of APOA5 was associated (P<0.05) with polyunsaturated fatty acids including eicosapentanoic acid (C20:5n3) and docosahexanoic (C22:6n3) and saturated fatty acid lauric acid (C12:0) in combined population (JFT, JTT, and GCS). Furthermore, pathway analysis showed that APOA5 belonged to phagosome and peroxisome proliferator-activated receptors (PPAR) signaling pathway. In conclusion, this analysis has identified APOA5 and related pathway crucial for fatty acid composition and metabolism in sheep, as well as this gene provide molecular marker to select sheepmeat with high unsaturated fatty acid.